2023
DOI: 10.1111/1756-185x.14964
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of baricitinib for the treatment of systemic lupus erythematosus patients: A meta‐analysis of randomized controlled trials

Aditya K. Panda,
Shovit Ranjan,
Jayanta K. Sahu

Abstract: BackgroundSystemic lupus erythematosus (SLE) is an autoimmune disorder characterized by abnormal autoantibody production, inflammation, and organ damage. Most SLE treatment strategies aim to induce remission or reduce disease activity while avoiding flares. Baricitinib has been used effectively to manage various inflammatory diseases, and some randomized controlled trials (RCT) have shown that it is beneficial in treating SLE. The current study aims to assess the efficacy of baricitinib in treating SLE patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The primary efficacy end point, SRI-4 at Week 52, was met in the BRAVE-I study (57% vs. 46%; p = .02) with baricitinib 4 mg but not in BRAVE-II (47.4% vs. 45.6%). Secondary end points that included SRI-4 response at Week In a recent issue of International Journal of Rheumatic Diseases, Panda et al 24 performed a meta-analysis of the above three RCTs 20,22,23 and reported that baricitinib 4 mg/day was superior to PBO in terms of achievement of SRI-4 but not LLDAS. Serious AEs were significantly more common with baricitinib 4 mg than PBO.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The primary efficacy end point, SRI-4 at Week 52, was met in the BRAVE-I study (57% vs. 46%; p = .02) with baricitinib 4 mg but not in BRAVE-II (47.4% vs. 45.6%). Secondary end points that included SRI-4 response at Week In a recent issue of International Journal of Rheumatic Diseases, Panda et al 24 performed a meta-analysis of the above three RCTs 20,22,23 and reported that baricitinib 4 mg/day was superior to PBO in terms of achievement of SRI-4 but not LLDAS. Serious AEs were significantly more common with baricitinib 4 mg than PBO.…”
mentioning
confidence: 99%
“…In fact, four other meta-analyses of the same RCTs were also published at round the same time period (August to November 2023). [25][26][27][28] Interestingly, the results from these five meta-analyses [24][25][26][27][28] are somewhat different. While a reduction in SLEDAI by ≥4 points and remission of skin/joint disease were significantly more frequent in the baricitinib 4 mg group 25,27,28 after data pooling, the superiority of baricitinib 4 mg to PBO in the SRI-4 response was only demonstrated in three meta-analyses 24,26,28 but not in the other two.…”
mentioning
confidence: 99%
See 2 more Smart Citations